Sporen uit het verleden : tien historische figuren uit onze streken. - Mogenet, Jean-Philippe, ....- (Averbode : Averbode, 2004)
Inhoud: Ambiorix Clovis Karel de Grote Godfried van Bouillon Jacob van Artevelde Karel V Aartshertogin Isabella Keizerin Maria-Theresia Napoleon Bonaparte Lepopold II
Keywords: België -- Geschiedenis